1982
DOI: 10.1007/bf01453005
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the solubilization mechanism of sodium octanoate micelles by small-angle X-ray scattering

Abstract: Abstract:The micellar radii and the electron density of the polar and non polar regions in micelles have been determined by a small-angle X-ray scattering (SAXS) technique originally designed by Luzzati et al. and subsequently modified by Larsson. The model employed shows the micellar structure as consisting of a liquid hydrocarbon core and a polar shell comprising the ionic polar head groups plus the diffuse double layer of bound counterions. The shortcomings of the model are discussed in the light of a recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…Considering the micelle radius (1.39 nm) it shows that the hydration layer protrudes into the rough micelle surface and constitutes a part of the semi-spherical micelle entity. These results support early small-angle X-ray investigations of the sodium octanoate micelle structure [79][80][81], although illustrated as radial structure parameters. A statistical analysis of water penetration in radially oriented monomers in micelle [104,106] resulted in an average micelle radius of 1.2 nm and an average micelle core of 1.16 nm in agreement with small-angle neutron scattering results [107,108].…”
Section: Accepted Manuscriptsupporting
confidence: 79%
See 1 more Smart Citation
“…Considering the micelle radius (1.39 nm) it shows that the hydration layer protrudes into the rough micelle surface and constitutes a part of the semi-spherical micelle entity. These results support early small-angle X-ray investigations of the sodium octanoate micelle structure [79][80][81], although illustrated as radial structure parameters. A statistical analysis of water penetration in radially oriented monomers in micelle [104,106] resulted in an average micelle radius of 1.2 nm and an average micelle core of 1.16 nm in agreement with small-angle neutron scattering results [107,108].…”
Section: Accepted Manuscriptsupporting
confidence: 79%
“…For sodium octanoate micelles equation (77a) predicted an aggregation number of 22. Assuming N = 11 the number of dry methylene groups are 4-5 which corresponds to a core radius of about 0.7 nm which is not far from the simulated one (0.5 nm, [22,23]) and that found with small-angle M A N U S C R I P T ACCEPTED MANUSCRIPT 39 X-ray scattering (0.45-0.60 nm, [79][80][81]) at cmc. Prolate (rod shaped micelle) growth may be considered a first step towards hexagonal liquid separation (cf.…”
Section: Models For Microemulsion Formation In Water -Surfactant (Mixmentioning
confidence: 94%
“…Zemb et al [44] have reported a radius of 1.08 nm in a light scattering experiment. Friman and Rosenholm [45] obtained a larger micellar radius using an X-ray scattering experiment, 1.8 nm. The agreement is quantitative considering that parameters derived from scattering experiments are obtained assuming particular features of the micellar system structure.…”
Section: åQvist Parameters For Sodium Cationmentioning
confidence: 99%
“…The methods used to estimate this quantity will be discussed below. We note that small-angle X-ray scattering (SAXS) has previously been used to study a similar system, NaCd/Octane-l,8-diol/H20 [7]. However, the analysis used in that study relied on using data only on the high-Q side of the interference peak in the scattered intensity and it was assumed that this part of the data was wholly due to the single-micelle form factor.…”
mentioning
confidence: 98%